Human Resources Challenges in Apparel Industry in Sri Lanka (Global Journal of Management and Business Research, 2020)
This study aims to identify the human resources challenges existing in the apparel sector of Sri Lanka and provide recommendations to secure with managing the barriers to go ahead with future sustainability in the industry. The research approach is qualitative and followed the case study method. Face to face interviews was the method of collecting data by following a semi-structured questionnaire for the research, and the data analysis method was the thematic analysis. The finding demonstrates nine core human resources challenges in the apparel industry in Sri Lanka.
Keywords: apparel industry; high competition; human resources challenges scarcity of labor